An mRNA expression atlas for the duck with public RNA-seq datasets - Qiuyu Tao; Anqi Huang; Jingjing Qi; Zhao Yang; Shihao Guo; Yinjuan Lu; Xinxin He; Xu Han; Shuaixue Jiang; Mengru Xu; Yuan Bai; Tao Zhang; et al. (BMC Genomics)
Abstract Background Ducks are globally important poultry species and a major source of farm animal products, including meat, eggs, and feathers. A thorough understanding of the functional genomic and transcriptomic sequences is crucial for improving production efficiency. Result This study constructed the largest duck mRNA expression atlas among all waterfowl species to date. The atlas encompasses 1,257 tissue samples across 30 tissue types, representing all major organ systems. Using advanced clustering analysis, we established co-expression network clusters to describe the transcriptional features in the duck mRNA expression atlas and, when feasible, assign these features to unique tissue types or pathways. Additionally, we identified 27 low-variance, highly expressed housekeeping genes suitable for gene expression experiments. Furthermore, in-depth analysis revealed potential sex-biased gene expression patterns within tissues and specific gene expression profiles in meat-type and egg-type ducks, providing valuable resources to understand the genetic basis of sex differences and particular phenotypes. This research elucidates the biological processes affecting duck productivity. Conclusion This study presents the most extensive gene expression atlas for any waterfowl species to date. These findings are of significant value for advancing duck biological research and industrial applications.